Artist's photo reference Reflections, textures & backgrounds - Greene, Gary. frey50 (Cincinnati, Ohio North Light Books, 2004)
From smooth stones in a riverbed, to light reflecting off satin, to a sunset over the desert sands, capturing reflections, textures and backgrounds is key to adding depth and interest to your work. In this comprehensive source, you'll find more than 475 photo references of common reflections, textures and backgrounds - images that will help you grasp these subjects so you can paint them realistically and skillfully.
Includes index.
Keywords: Photography, artistic; Reflections; Texture (Art); Painting from photographs